Adesão à terapia antirretroviral em pessoas vivendo com HIV que são atendidas pela Rede de Atenção Psicossocial de Campo Grande, Mato Grosso do Sul, 2014-2018 - PRISCILLA ARASHIRO (2021)
Human immunodeficiency virus (HIV) infection remains a major public health concern in Brazil. Brazilian clinical treatment protocol recommends the initiation of antiretroviral therapy (ART) to all HIV-positive adults, even without immune compromisse. Currently, one of the biggest challenges are related to adherence to ART. Consumption of alcohol and other drugs in people living with HIV (PLHIV) have been associated with decreased adherence or discontinuation of ART. Individuals with mental disorders are at increased risk exposure to sexually transmitted infections. In Brazil, there are few studies that bring together mental health and adherence to ART. Another aggravating factor concerns the lack of communication and the dissociated work of health services specialized in mental health and infectious diseases. Thus, this study aimed to evaluate the adherence to ART in PLHIV who were who attending the facilities care of the Psychosocial Care Network of Campo Grande, from January 2014 to December 2018. The epidemiological clinical profile of PLHIV with moderate or severe mental disorders, the therapeutic regimens, and the adherence to ART were assessed based on data reported to SINAN (Brazil Information System for Notifiable Diseases) and to medical records. The proportion of PLHIV with mental disorders moderate or severe, linked to the RAPS attention points, during the study period was 8.8 cases per 1000 PLHIV. The predominant epidemiological profile was male, white or brown, heterosexual, with incomplete primary education. Were found percentages of 40.2% of co-infections; 44.4% indication of drug abuse; 35.5% of ideations or suicidal thoughts. The most prevalent founded disorder was substance and alcohol abuse, followed by depressive and anxiety disorders. Our results showed the low adherence to the ART in PLHIV with mental disorders. The immunological therapeutic failure was significant associated with mental disorders and with the presence of co-infections. The low ART adherence was significant associated with: people experiencing homelessness, abusive use of alcohol and illicit drugs, irregular attending at health services specialized in mental health and infectious diseases. These findings are important to support the actions care workers and for the planning of improvements of the lines of care. In addition, these data could also support the strengthening the lines of care of the Brazilian Health Unic System. Keywords: mental health, mental disorders, antiretroviral therapy, adherence.